Prediction of a Potential Mechanism of Intervertebral Disc Degeneration Based on a Novel Competitive Endogenous RNA Network. (30th June 2021) - Huang, Junshen; Li, Yuxi; Ye, Ziwei; Cheng, Ziying; Huang, Jiajun; Lu, Shixin; Su, Kaihui; Liang, Yuwei; Li, Ming; Huang, Lin
Abstract : Low back pain which resulted from intervertebral disc degeneration (IDD) is a common health problem that afflicts people all over the world. Due to the lack of an overall understanding of the molecular interactions involved in IDD, we hope to better understand the pathogenetic mechanisms that drive the degenerative process. The purpose of this study is to obtain mRNAs, miRNAs, lncRNAs, and circRNAs associated with IDD gained from public databases and to establish an interaction network. According to the results of microarray analysis and bioinformatics analysis from the contrast of IDD and normal nucleus pulposus tissues, a total of 49 mRNAs, 10 miRNAs, 30 lncRNAs, and 4 circRNAs were obtained and a lncRNA/circRNA–miRNA–mRNA interaction network was constructed. NEAT1–miR-5100–COL10A1 and miR663AHG/HEIH/hsa-circ-0003600–miR-4741–HAS2/HYAL1/LYVE1 might be potential interaction axes of the molecular mechanism in IDD. The increased expression of NEAT1 might inhibit miR-5100 and subsequently upregulate the expression of COL10A1, which leads to IDD, while the increased expression of miR663AHG/HEIH/hsa-circ-0003600 might inhibit miR-4741 and indirectly upregulate HAS2/HYAL1/LYVE1, and leads to the protection from IDD. More interaction axes are to be exploited to provide theoretical bases for further study on IDD.